2022
DOI: 10.1101/2022.09.02.506244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parity modulates impact of BMI and Gestational Weight Gain on gut microbiota in human pregnancy

Abstract: Shifts in the gut microbiome have been implicated in mediating maternal metabolic adaptations to pregnancy. We investigated the impact of pre-pregnancy BMI (pBMI) and gestational weight gain (GWG) on pregnancy-associated remodeling of the maternal gut microbiome and infant colonization, and whether previous pregnancies modulated observed associations. We found that the gut microbiota of participants with higher pBMI changed less over the course of pregnancy in primiparous, but not multiparous participants This… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Recently, infants with older siblings were found to have a more mature gut microbiota at 1 year, which in turn was associated with a lower prevalence of food allergy. 46 However, recent papers indicate that parity modulates the maternal gut 47 , 48 and vaginal microbiota 49 during pregnancy, and thus could affect the microbiome transferred to the offspring. Analyses stratified by delivery mode and intrapartum antibiotics revealed clear birth mode-dependent temporal patterns, suggesting early effects seen mainly in infants delivered vaginally without antibiotics are likely of maternal origin transmitted during the delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, infants with older siblings were found to have a more mature gut microbiota at 1 year, which in turn was associated with a lower prevalence of food allergy. 46 However, recent papers indicate that parity modulates the maternal gut 47 , 48 and vaginal microbiota 49 during pregnancy, and thus could affect the microbiome transferred to the offspring. Analyses stratified by delivery mode and intrapartum antibiotics revealed clear birth mode-dependent temporal patterns, suggesting early effects seen mainly in infants delivered vaginally without antibiotics are likely of maternal origin transmitted during the delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The common differential bacteria of the two methods were used in further analyses. Based on the common differential bacteria, Spearman analysis was used to analyze the correlation between these bacteria and clinical factors (age, BMI, parity, PSRS36 scores, and PRAQ-R scores) [ 9 , [32] , [33] , [34] ] as well as intrapartum variables (highest temperature and duration of labor). Finally, a multivariable analysis of general liner model (GLM) was used to analyze the effect of LEA on gut microbiota with adjustment for possible confounders.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, parity and prepregnancy BMI have been identified as factors that can stimulate changes in maternal microbiota during pregnancy (Kennedy et al, 2022). Specifically, primiparous mothers with higher prepregnancy BMI experienced fewer changes in their microbial composition over the course of pregnancy than multiparous mothers.…”
Section: Gut Microbiome: a Possible Link Between Pnms And Adverse Out...mentioning
confidence: 99%
“…Conversely, other studies have reported different patterns of change or no significant alterations in the gut microbiome throughout pregnancy (DiGiulio et al., 2015). More recently, parity and prepregnancy BMI have been identified as factors that can stimulate changes in maternal microbiota during pregnancy (Kennedy et al., 2022). Specifically, primiparous mothers with higher prepregnancy BMI experienced fewer changes in their microbial composition over the course of pregnancy than multiparous mothers.…”
Section: Introductionmentioning
confidence: 99%